Pengaruh Terapi Kompres Hangat pada Tempat Penyuntikan terhadap Respon Nyeri pada Bayi Saat Imunisasi DPT Combo di PMB Pera Tahun 2025 - Kamelia Sinaga; Rolasnih Lilista Simbolon; Asnita Sinaga; Riza Novianti (Lembaga Pengembangan Kinerja Dosen, 2025)
According to WHO data (2023), global DPT immunization coverage has decreased due to the impact of the COVID-19 pandemic. Around 25 million children worldwide have not received complete DPT immunization in 2022, which is the highest figure in the last decade. Meanwhile, the 2023 Indonesian Health Profile noted that the coverage of complete DPT-HB-Hib immunization doses (three times) has only reached 85.3%, still below the national target of 95% (WHO, 2023). Giving warm compresses to babies who receive DPT immunization injections can cause a warm, comfortable and calming effect, in the form of touch that can cause the release of endorphins, thereby blocking the transmission of pain stimuli, and can also reduce redness and swelling at the DPT immunization injection site. (Runiari & Surinati 2012) The purpose of this study was to analyze the Effect of Warm Compress Therapy at the Injection Site on Pain in Infants During DPT Combo Immunization at PMB Pera, Medan Tuntungan District, Medan City. This type of research is a quasi-experimental study using the Post-test only control group design approach, namely to determine the effect of warm compress therapy at the injection site on pain responses in infants during DPT Combo immunization. The population in this study that will be used is 40 babies (20 babies for the experimental group and 20 babies for the control group). The sampling technique used is a non-probability sampling technique with a purposive sampling approach. The research instrument is a closed questionnaire that has been tested for validity and reliability. Data was analyzed using the Kolmogorov Smirnov statistical test to determine the distribution of data. Meanwhile, to compare the warm compress group with the control group using the Mann-Whitney test. Based on the results of data analysis with the Mann Whitney Test, the Symp.sig value of 0.000 <0.05 means that Ho is rejected. So it can be concluded that there is a significant effect between warm compress therapy at the injection site during DPT Combo immunization on pain responses in infants at PMB Pera, Medan Tuntungan District, Medan City, North Sumatra Province in 2025.